Ligand-exchange processes on solvated lithium cations: DMSO and water/DMSO mixtures - Pasgreta, Ewa; Puchta, Ralph; Galle, Michael; van Eikema Hommes, Nico; Zahl, Achim; van Eldik, Rudi (ChemPhysChem, 2007)
Solutions of LiClO in solvent mixtures consisting of dimethylsulfoxide (DMSO) and water, or DMSO and γ-butyrolactone, were studied by Li NMR spectroscopy (for complexation by cryptands in γ-butyrolactone as a solvent, see: E. Pasgreta, R. Puchta, M. Galle, N. J. R. van Eikema Hommes, A. Zahl, R. van Eldik, J. Incl. Phen., 2007, 58, 81-88). Chemical shifts indicate that the Li ion is coordinated by four DMSO molecules. In the binary solvent mixture of water and DMSO, no selective solvation is detected, thus indicating that on increasing the water content of the solvent mixture, DMSO is gradually displaced by water in the coordination sphere of Li. The ligand-exchange mechanism of Li ions solvated by DMSO and water/DMSO mixtures was studied using DFT calculations. Ligand exchange on [Li(DMSO)] was found to follow a limiting associative (A) mechanism. The displacement of coordinated H O by DMSO in [Li(HO)] follows an associative interchange mechanism. The suggested mechanisms are discussed in reference to available experimental and theoretical data. © 2007 Wiley-VCH Verlag GmbH & Co. KGaA.